Optimizing IPAS learning to improve learning outcomes through the application of the teaching at the right level approach integrated with quizizz - Darinda Sofia Tanjung; Nanda Julfa Rezeki; Lolly Jean C. Simbulas (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This classroom action research examined whether the Teaching at the Right Level (TaRL) approach could improve fourth-grade students' learning outcomes in IPAS, especially on the topic of ethnic and cultural diversity, at UPT SDN 066047 Medan Helvetia. The study involved 14 students and was conducted in two cycles. The mean score increased from 57 in the pre-cycle to 76 in Cycle I and 89 in Cycle II, while classical mastery improved from 43% to 79% and finally to 100%. The study addresses a gap in the Indonesian elementary education literature, where TaRL has been discussed more often in literacy and numeracy than in interdisciplinary IPAS learning for lower- and middle-grade students. Its contribution lies in showing how diagnostic grouping, focused reinforcement, and cycle-based reflection can be operationalized in a real classroom to improve conceptual understanding of a contextually meaningful IPAS topic. The findings suggest that TaRL is not only effective at improving test performance but also a useful adaptive pedagogical strategy for elementary classrooms with heterogeneous readiness levels. The study therefore provides empirical support for differentiated instruction in IPAS and offers a practical reference for teachers seeking more responsive classroom interventions.